2020
DOI: 10.1177/0706743720970863
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian 24-Hour Movement Guidelines and Psychological Distress among Adolescents: Les Directives canadiennes en matière de mouvement sur 24 heures et la détresse psychologique chez les adolescents

Abstract: Objective: The Canadian 24-Hour Movement Guidelines for Children and Youth recommend at least 60 minutes of physical activity per day, 2 hours or less of recreational screen time per day, and 9 to 11 hours of sleep per night for 5 to 13 years old and 8 to 10 hours per night for 14 to 17 years old. This study examined the association between meeting these guidelines and psychological distress among adolescents. Methods: The present cross-sectional sample included 6,364 students aged 11 to 20 years from the 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 60 publications
4
16
0
Order By: Relevance
“…The adherence to 24-Hour Movement Guidelines found in our study is higher than those found in the studies conducted with European [ 17 , 19 , 27 ] and Asian adolescents [ 14 , 21 , 26 ] and lower than several studies conducted in the United States (5.0%–9.4%) [ 16 , 22 , 23 ]. However, our results are similar to the results found in Canadian adolescents [ 15 , 18 , 28 , 29 , 30 , 31 , 32 , 33 ]. These results underline the importance of addressing these movement behaviours from an integrative and holistic approach to increase physical activity and sleep duration and decrease screen time [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The adherence to 24-Hour Movement Guidelines found in our study is higher than those found in the studies conducted with European [ 17 , 19 , 27 ] and Asian adolescents [ 14 , 21 , 26 ] and lower than several studies conducted in the United States (5.0%–9.4%) [ 16 , 22 , 23 ]. However, our results are similar to the results found in Canadian adolescents [ 15 , 18 , 28 , 29 , 30 , 31 , 32 , 33 ]. These results underline the importance of addressing these movement behaviours from an integrative and holistic approach to increase physical activity and sleep duration and decrease screen time [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, most existing studies have reported that less than 10% of adolescents met the 24-Hour Movement Guidelines [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. These aforementioned studies have found inconsistent results in the proportion of adolescents who meet the 24-Hour Movement Guidelines, which have ranged from 0.3% to 2.0% in Asian [ 14 , 21 , 26 ] 3.1% in South Americans [ 25 ], 2.2% to 9.4% in North Americans (ranging from 2.2% to 5.2% in Canadian and from 5.0% to 9.4% in American) [ 4 , 15 , 16 , 18 , 22 , 23 , 24 , 28 , 29 , 30 , 31 , 32 , 33 ], and from 1.7% to 2.2% in European [ 17 , 19 , 27 ]. Most adolescents met sleep duration recommendations [ 13 , 14 , 15 , 17 , 18 , 19 , 20 , 21 , 22 , 25 ,…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Although research to date has largely focused on relationships between movement behaviours and physical health outcomes (e.g., adiposity, cardiometabolic health, aerobic fitness), indicators of mental health have begun to see increased attention of late, particularly among adolescents. [3][4][5][6][7][8][9][10][11][12][13][14][15] Understanding the impact of movement behaviours on mental health during the adolescent period is of particular importance from a public health standpoint as this life stage is characterized by heightened stress 16 and represents the peak onset of mental health problems. 17,18 Mental health, however, has been proposed to exist on a continuum that considers not only adverse symptoms, but also positive attributes.…”
Section: Movement Behaviours and Mental Wellbeing: A Cross-sectional Isotemporal Substitution Analysis Of Canadian Adolescentsmentioning
confidence: 99%